The Presence of Antineutrophil Cytoplasmic Antibodies and Antiphospholipid Antibodies in Patients with Severe Acute Respiratory Syndrome Coronavirus 2: A Case-Control Study among Sudanese Patients - Mohammed Shams Aldeen; Musa Logman Masaad; Ayman Azhary; Abdulomez Suliman; Mohammed Ahmed Alziber; Motasim MohammedAhmed; Farag Alla Mohamed Aman; Salahaldeen Ismail; Nadir Abuzeid; Abdualmoniem O. Musa; Samuel Tekle Mengistu; Mohammed Elfatih Hamida (Interdisciplinary Perspectives on Infectious Diseases)
Patients infected with COVID-19 are at an increased risk for thrombosis, suggesting a possible role of COVID-19 in the induction of coagulopathy. This study aimed to investigate the presence of prothrombotic antineutrophil cytoplasmic antibodies (ANCA) and antiphospholipid antibodies (aPLs) in the course of COVID-19 infection and to correlate these markers with severity and fatality, suggesting that COVID-19-induced autoimmune thrombosis is a possible axis in the inflammatory circuit of this infection. To investigate this, we conducted a case-control study which included patients with a positive reverse transcription-polymerase chain reaction (RT-PCR) test of COVID-19 and a control group with negative COVID-19 PCR and antibody (IgG-IgM and IgA nucleoprotein) ELISA results. An indirect immunofluorescence assay using granulocyte biochips (Aesku slides from AESKU DIAGNOSTICS, Germany) was used to detect ANCA (IgG), as well as multiplex ELISA for the detection of antiphospholipid antibodies for all patients with COVID-19 and for the control group. The results revealed the detection of antiphospholipid antibodies (IgG) in one patient out of the 45 patients in the case group. 1/45(2.2%) and 7/45(15.6%) tested positive for ANCA. Five were men and two were females, with one case revealed to be positive for both aPL and ANCA. A cytoplasmic reaction on the eosinophil granulocytes was observed in 2 cases; both were positive for ANCA. Other markers (CRP, APTT, PT, INR, ESR, and neutrophil and lymphocyte counts) were included in the study, along with demographic data. No aPL or ANCA reactions were detected for any of the control groups. These findings suggest that aPL and ANCA may be induced during the course of inflammation in COVID-19 and possibly contribute to the disease’s severity and mortality.